2020
DOI: 10.2147/rmhp.s268876
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude, and Practices Regarding COVID-19 Among Chronic Illness Patients at Outpatient Departments in Ho Chi Minh City, Vietnam</p>

Abstract: Background The novel coronavirus disease (COVID-19) has become a major threat to human life around the world. This study aims to assess the knowledge, attitude, and practices regarding COVID-19 among people with chronic diseases at the outpatient departments in Ho Chi Minh City. Methods A cross-sectional study was carried out between February and March 2020 using a convenience sampling strategy in three hospitals in Ho Chi Minh City (HCMC) via the use of a structured se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
5
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 13 publications
13
68
5
14
Order By: Relevance
“…In China, the general public demonstrated good knowledge, positive attitudes and appropriate practices in taking preventive measures [ 11 ]. Similar findings were found in Palestine, Saudi Arabia and Vietnam studies [ 12 , 13 , 14 ]. In contrast, lower income countries such as Syria, Pakistan, Bangladesh and Philippines reported lower KAP scores [ 15 , 16 , 17 , 18 ].…”
Section: Introductionsupporting
confidence: 90%
“…In China, the general public demonstrated good knowledge, positive attitudes and appropriate practices in taking preventive measures [ 11 ]. Similar findings were found in Palestine, Saudi Arabia and Vietnam studies [ 12 , 13 , 14 ]. In contrast, lower income countries such as Syria, Pakistan, Bangladesh and Philippines reported lower KAP scores [ 15 , 16 , 17 , 18 ].…”
Section: Introductionsupporting
confidence: 90%
“… 20 The present study has also shown indifference with the studies done in Vietnam and of the Kingdom of Saudi Arabia which have shown being male to have an association with lesser knowledge. 21 , 22 This study has shown similarity as it has shown a significant decrease of knowledge with a 1-year increase in age as reported with the very similar study conducted among chronic patients in Addis Zeman hospital, North West part of Ethiopia, which has revealed age, illiteracy, rural resident and lower to have a significant association with poor knowledge too. 23 …”
Section: Discussionsupporting
confidence: 75%
“…Acceptance of a hypothetical COVID-19 vaccine was high (92%) in a study of Vietnamese health workers. 50 In our FGDs, some participants were willing to accept vaccination as a control strategy, whereas others pointed to futility and inappropriateness of what appeared to them as a stopgap solution, when the overwhelming problem was displacement from their homes.…”
Section: Covid-19 Prevention Effortsmentioning
confidence: 89%